Abelian tropical covers - Len, Yoav; Ulirsch, Martin; Zakharov, Dmitry (Mathematical Proceedings of the Cambridge Philosophical Society)
Abstract Let $\mathfrak{A}$ be a finite abelian group. In this paper, we classify harmonic $\mathfrak{A}$ -covers of a tropical curve $Γ$ (which allow dilation along edges and at vertices) in terms of the cohomology group of a suitably defined sheaf on $Γ$ . We give a realisability criterion for harmonic $\mathfrak{A}$ -covers by patching local monodromy data in an extended homology group on $Γ$ . As an explicit example, we work out the case $\mathfrak{A}=\mathbb{Z}/p\mathbb{Z}$ and explain how realisability for such covers is related to the nowhere-zero flow problem from graph theory.

Grammatik in Bewegung. Klammerstrukturen in Sätzen erforschen - Sperling, Sonja (Die Grundschulzeitschrift)

Towards a Rocket Chip Based Implementation of the RISC-V GPC Architecture - Luchterhandt, Lars; Nellius, Tom; Beck, Robert; Dömer, Rainer; Kneuper, Pascal; Müller, Wolfgang; Sadiye, Babak (MBMV 2023 - 26. Workshop "Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen“, MBMV 2023, Freiburg)
RISC-V has received worldwide acceptance in the industry and by the academic community. As of today, multiple RISC-V applications and variants are under investigation for embedded IoT systems, from resource-limited single-core processors up to multi-core systems for High-Performance Computing (HPC). Recently, the Grid of Processing Cells (GPC) platform has been proposed as a scalable parallel grid-oriented network of processor cores with local memories. This paper describes a prototype design of the GPC platform for hardware implementation at Register-Transfer Level (RTL) based on modified RISC-V Rocket processors with scratchpad memories. It introduces a scalable Chisel-based implementation of the modified Rocket cores with RTL generation and a functional test using Verilator simulation. This work also includes the adaptation of the Chipyard software toolchain to extend the compiler to multi-core grids with different local address spaces.

Interkulturelles Kapital - Pöllmann, Andreas (EEO Enzyklopädie Erziehungswissenschaften Online)

Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule (eBook)
Angesichts der aktuellen Arbeitsbedingungen in Wissenschaft und Hochschule – zwischen Qualifizierung, Selbstoptimierung und Prekarisierung – hangeln sich Wissenschaftler*innen jenseits unbefristeter Professuren von einem befristeten Arbeitsvertrag zum nächsten. Unter prekarisierten Arbeitsbedingungen stemmen sie einen Großteil der wissenschaftlichen Arbeit in Forschung und Lehre. Der Band diskutiert diese Verhältnisse der Wissensproduktion aus theoretischen, historischen, politischen wie empirischen Blickrichtungen, wobei der Fokus der Analysen über ungleichheitstheoretische erziehungs- und sozialwissenschaftliche Perspektivierungen sowie solche angrenzender disziplinärer Felder grundiert ist. Er leistet damit auch einen Beitrag zu den Bestrebungen, für bessere Arbeitsbedingungen an Hochschulen und in der Wissenschaft einzutreten.

Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule
Angesichts der aktuellen Arbeitsbedingungen in Wissenschaft und Hochschule – zwischen Qualifizierung, Selbstoptimierung und Prekarisierung – hangeln sich Wissenschaftler*innen jenseits unbefristeter Professuren von einem befristeten Arbeitsvertrag zum nächsten. Unter prekarisierten Arbeitsbedingungen stemmen sie einen Großteil der wissenschaftlichen Arbeit in Forschung und Lehre. Der Band diskutiert diese Verhältnisse der Wissensproduktion aus theoretischen, historischen, politischen wie empirischen Blickrichtungen, wobei der Fokus der Analysen über ungleichheitstheoretische erziehungs- und sozialwissenschaftliche Perspektivierungen sowie solche angrenzender disziplinärer Felder grundiert ist. Er leistet damit auch einen Beitrag zu den Bestrebungen, für bessere Arbeitsbedingungen an Hochschulen und in der Wissenschaft einzutreten.

Bedingungen der Wissensproduktion an Hochschulen und die Notwendigkeit ihrer disziplinären Bearbeitung - Leinfellner, Stefanie; Thole, Friederike; Sehmer, Julian; Simon, Stephanie (Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule)

Biographien in der Wissenschaft zwischen Qualifizierung, (Selbst-)Optimierung und Prekarisierung - Simon, Stephanie; Sehmer, Julian; Thole, Friederike; Leinfellner, Stefanie (Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule)

Asymptotics for the infinite Brownian loop on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Elliptic and Parabolic Equations)
Abstract The infinite Brownian loop on a Riemannian manifold is the limit in distribution of the Brownian bridge of length T around a fixed origin when $$T → +∞ $$ T → + ∞ . The aim of this note is to study its long-time asymptotics on Riemannian symmetric spaces G / K of noncompact type and of general rank. This amounts to the behavior of solutions to the heat equation subject to the Doob transform induced by the ground spherical function. Unlike the standard Brownian motion, we observe in this case phenomena which are similar to the Euclidean setting, namely $$L^1$$ L 1 asymptotic convergence without requiring bi- K -invariance for initial data, and strong $$L^{∞ }$$ L ∞ convergence.
Keywords: Applied Mathematics; Numerical Analysis; Analysis

Scheduling Periodic Segmented Self-Suspending Tasks without Timing Anomalies - Lin, Ching-Chi; Günzel, Mario; Shi, Junjie; Seidl, Tristan Taylan; Chen, Kuan-Hsun; Chen, Jian-Jia (2023 IEEE 29th Real-Time and Embedded Technology and Applications Symposium (RTAS))

Simulation Environment with Customized RISC-V Instructions for Logic-in-Memory Architectures

Probabilistic Reaction Time Analysis - Günzel, Mario; Ueter, Niklas; Chen, Kuan-Hsun; von der Brüggen, Georg; Chen, Jian-Jia (ACM Transactions on Embedded Computing Systems)
In many embedded systems, for instance, in the automotive, avionic, or robotics domain, critical functionalities are implemented via chains of communicating recurrent tasks. To ensure safety and correctness of such systems, guarantees on the reaction time, that is, the delay between a cause (e.g., an external activity or reading of a sensor) and the corresponding effect, must be provided. Current approaches focus on the maximum reaction time, considering the worst-case system behavior. However, in many scenarios, probabilistic guarantees on the reaction time are sufficient. That is, it is sufficient to provide a guarantee that the reaction does not exceed a certain threshold with (at least) a certain probability. This work provides such probabilistic guarantees on the reaction time, considering two types of randomness: response time randomness and failure probabilities. To the best of our knowledge, this is the first work that defines and analyzes probabilistic reaction time for cause-effect chains based on sporadic tasks.

Probabilistic Reaction Time Analysis - Günzel, Mario; Ueter, Niklas; Chen, Kuan-Hsun; von der Brüggen, Georg; Chen, Jian-Jia (ACM Transactions on Embedded Computing Systems)
In many embedded systems, for instance, in the automotive, avionic, or robotics domain, critical functionalities are implemented via chains of communicating recurrent tasks. To ensure safety and correctness of such systems, guarantees on the reaction time, that is, the delay between a cause (e.g., an external activity or reading of a sensor) and the corresponding effect, must be provided. Current approaches focus on the maximum reaction time, considering the worst-case system behavior. However, in many scenarios, probabilistic guarantees on the reaction time are sufficient. That is, it is sufficient to provide a guarantee that the reaction does not exceed a certain threshold with (at least) a certain probability. This work provides such probabilistic guarantees on the reaction time, considering two types of randomness: response time randomness and failure probabilities. To the best of our knowledge, this is the first work that defines and analyzes probabilistic reaction time for cause-effect chains based on sporadic tasks.

Guest Editorial: Special Issue on Systems Optimizations for DSP and AI Applications - Chen, Kuan-Hsun; Lin, Yung-Chia; Lee, Jenq-Kuen (Journal of Signal Processing Systems)

Rapid NVM Simulation and Analysis on Single Bit Granularity Featuring Gem5 and NVMain - Hölscher, Nils; Truong, Minh Duy; Hakert, Christian; Seidl, Tristan; Chen, Kuan-Hsun; Chen, Jian-Jia (2023 IEEE 12th Non-Volatile Memory Systems and Applications Symposium (NVMSA))

Timing-Aware ROS 2 Architecture and System Optimization - Teper, Harun; Betz, Tobias; Von Der Brüggen, Georg; Chen, Kuan-Hsun; Betz, Johannes; Chen, Jian-Jia (2023 IEEE 29th International Conference on Embedded and Real-Time Computing Systems and Applications (RTCSA))

Buildings, valuated matroids, and tropical linear spaces - Battistella, Luca; Kühn, Kevin; Kuhrs, Arne; Ulirsch, Martin; Vargas, Alejandro (Journal of the London Mathematical Society)
Abstract Affine Bruhat–Tits buildings are geometric spaces extracting the combinatorics of algebraic groups. The building of parameterizes flags of subspaces/lattices in or, equivalently, norms on a fixed finite‐dimensional vector space, up to homothety. It has first been studied by Goldman and Iwahori as a piecewise‐linear analogue of symmetric spaces. The space of seminorms compactifies the space of norms and admits a natural surjective restriction map from the Berkovich analytification of projective space that factors the natural tropicalization map. Inspired by Payne's result that the analytification is the limit of all tropicalizations, we show that the space of seminorms is the limit of all tropicalized linear embeddings and prove a faithful tropicalization result for compactified linear spaces. The space of seminorms is in fact the tropical linear space associated to the universal realizable valuated matroid.

Du Val Singularities - Burban, Igor (Springer Proceedings in Mathematics & Statistics)

Du Val Singularities - Burban, Igor (Springer Proceedings in Mathematics & Statistics)

Privacy in the Age of Neurotechnology: Investigating Public Attitudes towards Brain Data Collection and Use - Kablo, Emiram; Arias Cabarcos, Patricia (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)